Discovering Patterns in Online Reviews of Beijing and Lisbon Hostels - Brochado, Ana (2022)
Brochado, A., Rita, P., & Moro, S. (2019). Discovering Patterns in Online Reviews of Beijing and Lisbon Hostels. Journal of China Tourism Research, 15(2), 172-191. https://doi.org/10.1080/19388160.2018.1543065